Study on Virulence Factors of Escherichia Coli Isolates of Buffalo Meat Origin - Kaskhedikar, S.; Chhabra, Daljeet; Sharda , R. (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
The global increase in food-borne diseases poses major challenges to health delivery and consequently economic well being of all nations, particularly the developing countries. 29 E. coli strains isolated from total 50 buffalo meat samples were tested for colonization factors (HA, Salt aggregation test and Congo red dye binding assay). Out of total 29 E. coli strains isolated from buffalo meat, 24 (82.75%) strains exhibited MSHA and 18 (62.06%) strains exhibited MRHA, 14 (48.27%) were positive for congo red dye binding and 11 (37.93%) isolates were positive for salt aggregation test.